Examination of level of knowledge in Italian general practitioners attending an education session on diagnosis and management of the early stage of Alzheimer's disease: pass or fail?. (28th January 2016) - Veneziani, Federica; Panza, Francesco; Solfrizzi, Vincenzo; Capozzo, Rosa; Barulli, Maria Rosaria; Leo, Antonio; Lozupone, Madia; Fontana, Andrea; Arcuti, Simona; Copetti, Massimiliano; Cardinali, Valentina; Grasso, Alessandra; et al.
ABSTRACT: Background: We detected the general level of knowledge about the early diagnosis of Alzheimer's disease (AD) and subsequent care in general practitioners (GPs) from Southern Italy. We explored also the GP perception about their knowledge and training on diagnosis and management of AD. Methods: On a sample of 131 GPs, we administered two questionnaires: the GP-Knowledge, evaluating GPs' expertise about AD epidemiology, differential diagnosis, and available treatments, and the GP-QUestionnaire on Awareness of Dementia (GP-QUAD), assessing the GPs' attitudes, awareness, and practice regarding early diagnosis of dementia. Results: Specific screening tests or protocols to diagnose and manage dementia were not used by 53% of our GPs. The training on the recognition of early AD signs and symptoms was considered inadequate by 55% of the participants. Females were more likely to consider their training insufficient (58%) compared to males (53%). Female GPs were less likely to prescribe antipsychotic drugs to control neuropsychiatric symptoms (NPS) and suggest specialist advice in late stage of cognitive impairment. Multiple Correspondence Analysis (MCA) performed only on GP-QUAD suggested two dimensions explaining 26.1% ("GP attitude") and 20.1% ("GP knowledge") of the inertia for a total of 46.2%, Conclusion: In our survey on GP clinical practice, several problems in properly recognizing early AD symptoms and subsequently screening patients to be referred to secondary/tertiary care centers for diagnosis confirmation have emerged. In the future, specific training programs and educational projects for GPs should be implemented also in Italy to improve detection rates and management of dementia in primary care.